(untitled) (Gestión y Gerencia, 2019)
CONTENT Editorial……………………………………………………………………….………...... i Articles VILLALOBOS, Aldrin y PÉREZ, Juan José Partial adaptation of the venezuelan company in an environment of regulations and controls. Periodo: 2010-2015………………………………………………………...……….… 1 MENDOZA, Yohana The positive and postpositive conception of science in the construction of contemporary management thinking …………………………………………………………...…...........……. 27 SÁNCHEZ, Juan Carlos y VALDIVÉ, Carmen Proximities when actuating epistemic-cognitive mathematics. Prelude that springs from testimonies of novice and expert mathematicians. An exploratory study………..…………. 50 FLORES, Leydi Yohanna Identification of organizational practices for the accumulation of knowledge and information management tools ………...……………………………………………..….…..…. 87 ZERPA, Saicidy; ROSALES, Maritza y MORALES, Odalis Applied accounting of the public and business sectors in Venezuela ….…………..……… 99 104 SAENZ, José A.; CAMACHO, Leylan y MENDOZA, Gaudis A Hazard analysis and critical control point (haccp) in a company balanced food for animals …….........................................…………………………………………....……..…..… 124 PERNÍA, Juan Carlos Training management in university centers under a values approach …….………..……… 152 CALLES, José Obstacles to achieve productive efficiency in venezuelan companies. Period: 2007-2015…………………........................................................................................................... 168 Publication standards …………..……….…..……….………………….………….…...……. 197